2015
DOI: 10.1515/jppr-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silvicultural techniques on the diversity of microorganisms in forest soil and their possible participation in biological control of Armillaria and Heterobasidion

Abstract: Effects of different pre-planting soil preparations and post-harvest wood debris applications in a clear-cut Scots pine plantation, on the abundance, diversity, and activity of culturable microorganisms were investigated. The investigation was done 9 years after the re-plantings had been done. This formed part of an investigation of silvicultural practices for conservation and the biological control ofArmillariaandHeterobasidionin northern temperate forests (Poland). The treatments being compared, were expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Woody debris incorporated into the top soil, providing nutrients in the first 10 years, improved tree growth, while the removal of woody debris improved tree health. Better health of trees in soil 2 could have resulted from: (a) absence of Armillaria ostoyae and Heterobasidion annosum , which could be suppressed by the abundant mycobiota (Kwaśna, Walkowiak, Łakomy et al, ), and (b) more efficient photosynthesis, as an effect of the higher proportion of mycorrhiza.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Woody debris incorporated into the top soil, providing nutrients in the first 10 years, improved tree growth, while the removal of woody debris improved tree health. Better health of trees in soil 2 could have resulted from: (a) absence of Armillaria ostoyae and Heterobasidion annosum , which could be suppressed by the abundant mycobiota (Kwaśna, Walkowiak, Łakomy et al, ), and (b) more efficient photosynthesis, as an effect of the higher proportion of mycorrhiza.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in soil fungal communities in managed and unmanaged forests or across temperate forest ecosystems have been studied in Germany (Goldmann et al, ; Wubet et al, ; Yurkov, Kemler, & Begerow, ) and in France (Buée et al, ). In Poland, the abundance and diversity of microorganisms in forest soils after different post‐harvest woody debris applications and pre‐planting soil preparations have been studied by Kwaśna, Łakomy, Gornowicz, Behnke‐Borowczyk et al, (), Kwaśna, Łakomy, Gornowicz, Mikiciński et al, (), Kwaśna, Walkowiak, Łakomy et al, (), Małecka & Kwaśna, () and Małecka, Kwaśna, & Szewczyk, (). The classical soil‐dilution method used by Kwaśna, Łakomy, Gornowicz, Mikiciński et al, () and Kwaśna, Walkowiak, Łakomy et al () enabled detection of active microfungi from the Ascomycota and Zygomycota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that biotic and abiotic soil attributes influence the suppression of plant diseases (Barros et al, ; Silva et al, ; Silva et al, ). However, biological factors were described as predominant in the suppression of most plant diseases caused by soil‐borne pathogens (Kwaśna et al, ). Other factors, such as increased organic matter content and recycling of macro and micronutrients that improve soil fertility, influence pH change and may increase the production by the plant of substances antagonistic to phytopathogens (Sales Júnior, Senhor, Michereff, & Medeiros, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may be involved in the interaction of soil attributes with the pathogen; however, organic matter and microbial populations are two major factors involved in the suppression of plant diseases caused by soil pathogens (Kwaśna et al, ). Nonetheless, there is still a gap in knowledge regarding the enzymatic activities involved in these systems, since these represent the link between organic matter degradation and microbial populations, and they may provide a sensitive tool for detecting changes in the soil (Medeiros et al, ).…”
Section: Introductionmentioning
confidence: 99%